Playful and practical activities in science education: didactic sequence about heat and temperature (Research, Society and Development, 2020)
Traditional classes in the field of the natural sciences in basic education are often uninteresting and monotonous and lack differentials to encourage students in the process of teaching and learning. In seeking to promote a better use in the natural sciences classes can make use of practices and play activities providing means to experience a positive and constructive interaction taking into subsunssores against the students. The objective of this study was to investigate previous knowledge of Science focusing on physics and the utilization of practical and playful activities in this process, developed in two 9th year elementary school class of in an estate school in Jaciara – MT. A questionnaire was applied to students, with objective and essay questions, related to their knowledge regarding physics (Science). Analyzing the data it was noticed that students already bring a previous knowledge on Physics, which is essential for the establishment of a meaningful learning. However, in most cases the students can’t relate Physics with other contents in Science and everyday matters. In order to streamline some contents of Science related to Physics, classes with playful and practical activities were done (with simple material and low cost) and focusing on the content of heat and temperature. An educational trail between the two groups (competition) with questions related to the content addressed through dialogue and practical scripts in class were also done. It was found that the application of a demonstrative and practical methodology in Science classes helped in the process of teaching and learning the contents covered, providing greater interaction and relaxation for students, addressing different levels of understanding and performance, thus favoring the achievement of knowledge exposed.